Effects of Dietary Protein and Energy on Growth Performance and Carcass Characteristics of Betong Chickens (Gallus domesticus) During Growing Period - Nguyen, Tuan Van; Bunchasak, Chaiyapoom; Chantsavang, Somchai (International Journal of Poultry Science, 2010)
The objective of this study was to investigate the requirements of protein and energy level of the Betong chicken during growing period (42-84 days of age). Total of 288 42-days old of Betong chickens were used in a 4 x 2 factorial experiment with a completely randomized design. Two factors are included in the experiment design: 1) four dietary protein levels (15, 17, 19 and 21% CP) and 2) two dietary energy contents (3,000 and 3,200 ME kcal/kg). The chicks were allocated in floored pen. Feed and water were provided to the chicks ad libitum through an experimental period. There was no significant interaction effect between protein and energy levels on growth performance and carcass yields of the birds. Dietary protein level of 19-21% CP and energy content of 3,000 ME kcal/kg were sufficient for the best performance and carcass quality of the Betong chicken. In conclusion, dietary protein levels of 19% CP and energy content of 3,000 ME kcal/kg are recommended for the birds.